Concept of a Multi-agent Based Decentralized Production System for the Automotive Industry - Blesing, Christian; Luensch, Dennis; Stenzel, Jonas; Korth, Benjamin (Advances in Practical Applications of Cyber-Physical Multi-Agent Systems: The PAAMS Collection, 2017)
To face the challenges of today’s market requirements, a huge effort is made to plan continuous flow manufacturing systems used today. Simultaneously disturbances during the production have decisive negative effects on the effectiveness. To mitigate this problem, current research programs try to use flexible production systems with a high degree of self-organization. In this paper a novel concept for a flexible decentralized production system is described which combines the planning method of a precedence graph and a multi-agent-system that forms a modular control system. Furthermore first results are presented that have been achieved by a pilot demonstrator and simulation experiments.